Meningkatkan Kepercayaan Diri melalui Bimbingan Kelompok Teknik Sosiodrama - Dita Ayu Pratiwi; Arifin Nur Budiono; Fakhruddin Mutakin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2019)
Confidence is the key to self motivation. Individuals will not live a good life without any confidence. Researchers conducted observations in MTs ASHRI Jember class VIII A academic year 2017-2018 and the result of pretest is 42% which is classified in the qualification is less and still bellow the average of ideal confidence. This study aims to increase self confidence through group guidance services with sociodrama techniques. The type of research used is action research guidance and counseling (PTBK). The procedure used is the cycle model. Based on the result of research on the implementation of the cycle of  I respondents still showed an attitude of lack confidence. It shown from not nervous when appearing in front of the class, feeling confident that they can, dare in eksplore role and do not look shy embarrassment that only around 50%. And in the IInd cycle began to show an increasein confidence in student this is seen in not nervous when appearing in front of the class, feel confident that they can, dare in eksplore role and do not look shy embarrassment that only ranges between 75%. Thus it can be concluded that the service of group guidance with sociodrama technique can improve self confidence of class VIII A MTs ASHRI Jember. Keywords: Self confidence, Sociodrama.